Pengembangan LMS Berbasis Problem-Based Learning untuk Meningkatkan Hasil Belajar pada Elemen Algoritma Pemrograman - Salsabilla Sukma Masayu; Rindu Puspita Wibawa (CV. SINAR HOWUHOWU, 2026)
Learning in the Programming Algorithms element at vocational high schools still faces challenges, including the use of digital learning media that are not yet integrated, limited student engagement, and low learning outcomes. This study aimed to develop a Learning Management System (LMS) based on Problem-Based Learning (PBL) and to determine its feasibility and effectiveness in improving the learning outcomes of tenth-grade students at SMK Sejahtera Surabaya. The study employed a Research and Development (R&D) method using the ADDIE development model and a Nonequivalent Control Group Design. The research was conducted at SMK Sejahtera Surabaya with tenth-grade students as the research subjects, consisting of experimental and control classes. Data were collected through expert validation, learning achievement tests, and the Short User Experience Questionnaire (UEQ-S), and were analyzed using percentage analysis, the Mann–Whitney test, and N-Gain analysis. The results showed that the LMS achieved a validity score of 94.12%, indicating a highly valid category. The UEQ-S results also showed a positive user experience with a Good category. Furthermore, the Mann–Whitney test yielded a significance value of 0.004 (<0.05), while the average N-Gain score of the experimental class (0.581) was higher than that of the control class (0.369). Therefore, the developed PBL-based LMS is feasible for use and effective in improving students' learning outcomes in the Programming Algorithms element.